2015
DOI: 10.1002/clen.201400366
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phenol by Immobilization of Trametes versicolor in Silica–Alginate–Fungus Biocomposites and Loofa Sponge

Abstract: Research Article Removal of Phenol by Immobilization of Trametes versicolor in Silica-Alginate-Fungus Biocomposites and Loofa SpongeWhite-rot fungi have potential in organic pollutant degradation. Immobilization of microorganisms has been successfully used for bioremediation. In this work, 25 isolates of Argentinean white-rot fungi were tested for their tolerance toward up to 10 mM phenol in agar plates. Seven isolates were further evaluated for their ability to grow on plates with 2,6-dimethoxyphenol, gallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
8
0
2
Order By: Relevance
“…Crude extract enzyme immobilizedDegradation of emerging endocrine disruptor (bisphenol A)800 μL McIlvaine buffer (pH 3), 100 µL of ABTS (5 mM, 1.0% w/v) and 100 µL of laccase extract of P. sanguineus (CS43)100% degradation of bisphenol A (20 mg/L) was achieved in less than 24 hProbably degradation ends in the formation of 4-isopropenylphenol[42] Trametes versicolor BAFC 2234MI7-days cultures in 30-L STR with complex liquid medium (50% tomato juice). Purified enzymesIn vitro oxidation of phenolThe reaction mixture in 1.5-mL contained dissolved phenol (0.5 mM), 50 mM sodium citrate pH 4.5 and 0.1 U/mL laccase84% phenol removal in 4 h. Dark colored products partly precipitated were foundOxidative coupling of phenoxy radicals as major pathway of phenol conversion[43] Recombinant laccase from Trametes sanguineus in Trichoderma atroviride FCultures grown in 50 mL, incubated for 4 days at 28 °C/150 rpm. Purified laccaseDegradation of xenobiotic compounds (phenanthrene and benzo[α]pyrene)Phenanthrene and benzo[α]pyrene were added into supernatants up to at 10 ppm, incubated at 28 °C and shaken at 150 rpm for 24 h57.5 U/L of laccase in supernatant removed phenanthrene and benzo[α]pyrene (97 and 99% respectively) present in wastewater from a biofuel industry plantNot reported[67] Nicotiana tabacum expressing a laccase from Pleurotus ostreatus CPlants were grown for 16 days in a growing chamber at 24 °C under a photoperiod of 16:8 h (light:darkness).…”
Section: Sources Of Laccases That Are Useful In Water Bioremediationmentioning
confidence: 99%
See 2 more Smart Citations
“…Crude extract enzyme immobilizedDegradation of emerging endocrine disruptor (bisphenol A)800 μL McIlvaine buffer (pH 3), 100 µL of ABTS (5 mM, 1.0% w/v) and 100 µL of laccase extract of P. sanguineus (CS43)100% degradation of bisphenol A (20 mg/L) was achieved in less than 24 hProbably degradation ends in the formation of 4-isopropenylphenol[42] Trametes versicolor BAFC 2234MI7-days cultures in 30-L STR with complex liquid medium (50% tomato juice). Purified enzymesIn vitro oxidation of phenolThe reaction mixture in 1.5-mL contained dissolved phenol (0.5 mM), 50 mM sodium citrate pH 4.5 and 0.1 U/mL laccase84% phenol removal in 4 h. Dark colored products partly precipitated were foundOxidative coupling of phenoxy radicals as major pathway of phenol conversion[43] Recombinant laccase from Trametes sanguineus in Trichoderma atroviride FCultures grown in 50 mL, incubated for 4 days at 28 °C/150 rpm. Purified laccaseDegradation of xenobiotic compounds (phenanthrene and benzo[α]pyrene)Phenanthrene and benzo[α]pyrene were added into supernatants up to at 10 ppm, incubated at 28 °C and shaken at 150 rpm for 24 h57.5 U/L of laccase in supernatant removed phenanthrene and benzo[α]pyrene (97 and 99% respectively) present in wastewater from a biofuel industry plantNot reported[67] Nicotiana tabacum expressing a laccase from Pleurotus ostreatus CPlants were grown for 16 days in a growing chamber at 24 °C under a photoperiod of 16:8 h (light:darkness).…”
Section: Sources Of Laccases That Are Useful In Water Bioremediationmentioning
confidence: 99%
“…Fungal laccases aid bioremediation through the oxidation of polycyclic aromatic hydrocarbons (PAHs) [39, 40], plastics and phenolic compounds [4144], dyes [4448], and the degradation of pharmaceutically active compounds [4952], among others (Table 1). Given that laccases from white-rot fungi have the potential for phenolic compound degradation, different studies have involved the immobilization of microorganisms, such as T. versicolor , into silica-alginate and loofa sponges as supports for phenol removal [43]. While crude extract from Trametes pubescens has been used for the degradation of chlorophenols (Table 1) [44].…”
Section: Sources Of Laccases That Are Useful In Water Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different screening techniques were carried out to select strains with polycyclic aromatic hydrocarbons, dyes and phenols biodegradation capabilities (Levin et al 2004; Matsubara et al 2006; Lee et al 2014; Carabajal et al 2016). However, plate screening has not been yet evaluated as a quick technique to select strains capable of tolerating and degrading PCBs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported enhanced petroleum hydrocarbon degradation by immobilized hydrocarbon-degrading bacteria compared to free-living cells [17,18]. This observation has increase the interest in immobilization of microbial cells for bioremediation purposes.…”
Section: Introductionmentioning
confidence: 99%